UPR artificial stone damp-heat-resistant yellowing accelerant composition as well as preparation method and application of UPR artificial stone damp-heat-resistant yellowing accelerant composition

By using specific accelerator compositions in UPR artificial stone, the problem of yellowing in high temperature and high humidity environments is solved, which significantly improves its moisture and heat resistance and appearance stability, and enhances market competitiveness.

CN119461944APending Publication Date: 2025-02-18ZHUHAI SHENGXIYUAN MECHANICAL & ELECTRICAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411293901.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

UPR artificial stone is prone to yellowing in high temperature and high humidity environments, affecting its aesthetic appearance and service life.

Method used

UPR artificial stones with moisture and heat resistant yellowing composition, the composition includes a main catalytic accelerator, a synergist, a yellowing inhibitor, a thickener, water, a functional additive and a diluent, through specific The ratio and preparation method are used to form an organic phase dispersion or an organic phase solution, and improve the moisture and heat resistance of the resin.

Benefits of technology

It significantly improves the moisture-heat yellowing performance of UPR artificial stone, making it less likely to turn yellow in high temperature and high humidity environments, keeping the external light color for a long time, and enhancing its market competitiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005045369010000061
    Figure BDA0005045369010000061
  • Figure BDA0005045369010000101
    Figure BDA0005045369010000101
  • Figure BDA0005045369010000102
    Figure BDA0005045369010000102
Patent Text Reader

Abstract

The invention provides a damp-heat-yellowing-resistant accelerant composition for UPR artificial stone as well as a preparation method and application of the damp-heat-yellowing-resistant accelerant composition. The accelerant composition comprises 3.0 to 35.0 percent by weight of a main catalytic accelerant, 0.0 to 30.0 percent by weight of a synergist, 55.0 to 97.0 percent by weight of a yellowing-resistant inhibitor, 0.0 to 2.0 percent by weight of a thickening agent, 0.0 to 3.0 percent by weight of water, 0.0 to 1.0 percent by weight of a functional additive and the balance of a diluent, wherein the anti-yellowing inhibitor comprises a component A, and the component A is one or more of organic carboxylic acid sodium salt, organic carboxylic acid potassium salt and organic carboxylic acid calcium salt; the accelerant composition enables the prepared UPR artificial stone to have good damp-heat yellowing resistance, solves the application problem of visual difference caused by appearance color change due to the fact that the UPR artificial stone is prone to aging and yellowing, and can be widely applied to production of artificial stone products of a UPR unsaturated resin system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of artificial stones, and in particular to an accelerator composition for UPR artificial stones resistant to wet-heat yellowing, and a preparation method and application thereof. Background Art

[0002] UPR (Unsaturated Polyester Resin) artificial stone is an artificial stone made of unsaturated polyester resin as the base material, by adding fillers (such as aluminum hydroxide, calcium carbonate, etc.), additives (such as curing agent, accelerator, defoaming agent, etc.) and pigments, and through vacuum mixing, casting, curing and other processes. UPR artificial stone has been widely used in interior decoration projects due to its non-toxicity, flame retardancy, easy processing, good decorative effect and other characteristics.

[0003] Although UPR artificial stone has many advantages, it also exposes some problems during use, especially its poor resistance to yellowing under heat and humidity. In a high temperature and high humidity environment, UPR artificial stone is prone to yellowing, which seriously affects its appearance and service life. The yellowing problem is mainly due to the fact that the unsaturated double bonds in the UPR resin are prone to oxidation under conditions such as light, oxygen, and heat, causing the resin color to turn yellow. In view of the problem that UPR artificial stone has poor resistance to yellowing under heat and humidity, it is particularly important to develop an effective accelerator composition for yellowing under heat and humidity resistance. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides an accelerator composition for UPR artificial stone resistance to moisture and heat yellowing, and a preparation method and application thereof. The accelerator composition can improve the moisture and heat yellowing resistance of UPR artificial stone.

[0005] The technical solution of the present invention is achieved in this way:

[0006] A UPR artificial stone accelerator composition for resistance to wet-heat yellowing, characterized in that:

[0007] According to weight percentage, the promoter composition includes: 3.0-35.0%wt of a primary catalytic promoter, 0.0-30.0%wt of a synergist, 55.0-97.0%wt of a yellowing inhibitor, 0.0-2.0%wt of a thickener, 0.0-3.0%wt of water and 0.0-1.0%wt of a functional additive, and the balance is a diluent;

[0008] The anti-yellowing inhibitor includes component A, and component A is one or more of organic carboxylic acid sodium salt, organic carboxylic acid potassium salt, and organic carboxylic acid calcium salt.

[0009] Preferably, ingredient A is one or more of potassium isooctanoate, sodium isooctanoate, and calcium isooctanoate.

[0010] Preferably, the anti-yellowing inhibitor is an organic phase dispersion or organic phase solution formed by mixing component A and organic solvent B, the solid content of component A is 3.0-15.0%wt, and the organic solvent B is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid.

[0011] Preferably, the main catalyst promoter is an organic phase dispersion or organic phase solution formed by mixing a metal carboxylate and an organic solvent C, the solid content of the metal carboxylate is 3.0 to 15.0% wt, and the organic solvent C is at least one of a benzene organic solvent, a ketone organic solvent, an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and an organic carboxylic acid.

[0012] Preferably, the metal carboxylate is one or more of iron naphthenate, cobalt naphthenate, manganese naphthenate, cobalt isooctanoate, zinc isooctanoate, zinc neodecanoate, and manganese neodecanoate. The metal carboxylate is mainly a salt of naphthenic acid, isooctanoic acid, and neodecanoic acid with metal iron (Fe), cobalt (Co), manganese (Mn), and zinc (Zn), and preferably one or more of cobalt naphthenate and cobalt isooctanoate are used.

[0013] Preferably, the synergist is an organic phase dispersion or organic phase solution formed by mixing an organic carboxylate copper salt and an organic solvent D, the organic carboxylate copper salt is one or more of copper acetate and copper isooctanoate, the solid content of the organic carboxylate copper salt is 3.0 to 12.0%wt, and the organic solvent D is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid.

[0014] Preferably, the thickener is one or more of ethyl cellulose (CE), cellulose acetate butyl (CAB), and fumed silica. The main function of the thickener is to serve as a linker skeleton material of the accelerator composition, thereby improving the stability of the accelerator and preventing the precipitation and sedimentation of metal salts.

[0015] Preferably, distilled water or deionized water is used as water, and its main function is to improve the solubility or dispersibility of the metal salt in the organic phase.

[0016] Preferably, the functional additive is one or more of a dispersant, a leveling agent, and an odor masking agent, which is used to improve or enhance the specific properties of the accelerator composition.

[0017] Preferably, the diluent is an organic solvent such as alcohols, esters, alcohol ethers, etc., preferably a solvent with a higher polarity, including one or more of methanol, ethanol, n-propanol, isopropanol, tert-butanol, n-pentanol, isohexanol, n-octanol, isooctyl alcohol, diacetone alcohol, ethylene glycol methyl ether, ethylene glycol monobutyl ether, diethylene glycol monobutyl ether, ethyl acetate, and n-butyl acetate, which functions to dilute the accelerator composition.

[0018] Another object of the present invention is to provide a method for preparing a UPR artificial stone accelerator composition resistant to wet and hot yellowing, which comprises the following specific steps: firstly, a main catalytic accelerator, a synergist and a yellowing resistance inhibitor are measured and added into a dispersion container in sequence according to a formula ratio, and dispersed for 10 to 30 minutes at a speed of 200 to 1000 r / min under an environment of 15 to 35° C.; then, a thickener is added and dispersed for 30 to 60 minutes, and then water, a functional additive and a remaining amount of a diluent are added in sequence and dispersed for 10 to 30 minutes, and finally, the accelerator composition is filtered through a filter screen of 100 to 300 meshes to obtain the accelerator composition.

[0019] Another object of the present invention is to use the above-mentioned UPR artificial stone accelerator composition for resistance to wet-heat yellowing or the accelerator composition prepared by the above-mentioned preparation method in the preparation of UPR artificial stone.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] The UPR artificial stone accelerator composition for resistance to wet-heat yellowing of the present invention is added with one or more of organic carboxylic acid sodium salt, organic carboxylic acid potassium salt and organic carboxylic acid calcium salt in the formula, so that the prepared UPR artificial stone has good resistance to wet-heat yellowing, solves the application problem of visual difference caused by the change of appearance color due to easy aging and yellowing of the color of the UPR artificial stone, and can be widely used in the production of artificial stone products of the UPR unsaturated resin system, so that the UPR artificial stone is not easy to yellow, is resistant to weather aging such as wet-heat, and has excellent long-term retention of external light color, showing excellent competitiveness for the application of the UPR artificial stone in the market. DETAILED DESCRIPTION

[0022] The embodiments described below in conjunction with the present invention are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1

[0024] A UPR artificial stone accelerator composition (accelerator 1A) for resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0025] Table 1 Formula of accelerator 1A in Example 1 of the present invention

[0026] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt isooctanoate organic phase dispersion or organic phase solution with a solid content of 12.0%wt 10%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 0.1%wt Anti-yellowing inhibitor Sodium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 65%wt Thickener Fumed Silica 1.0%wt Thinner Isopropyl alcohol margin

[0027] The organic solvent (organic solvent B) in the main catalyst promoter is at least one of a benzene organic solvent, a ketone organic solvent, an alcohol organic solvent, an ester organic solvent, and an ether organic solvent. In this embodiment, the organic solvent is isooctanoic acid;

[0028] The organic solvent (organic solvent C) in the synergist is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid. In this embodiment, the organic solvent is isooctanoic acid;

[0029] The organic solvent (organic solvent D) in the anti-yellowing inhibitor is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid. In this embodiment, the organic solvent is isopropyl alcohol.

[0030] A UPR artificial stone accelerator composition (accelerator 1A) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0031] Preparation: Prepare the raw materials according to the formula ratio;

[0032] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0033] Filtration: Filter through a 100-300 mesh filter to produce Accelerator 1A.

[0034] The accelerator composition is applied to UPR artificial stone. In this embodiment, UPR artificial stone is made to verify the effect of accelerator 1A. The UPR artificial stone experimental test block (test block 1A) is prepared according to the following method:

[0035] The UPR artificial stone experimental test block (test block 1A) was prepared by blending a liquid resin mixture at room temperature, wherein the liquid resin mixture consisted of 350g of unsaturated resin (Xinshuangli Huizhou Resin Co., Ltd., 5288 phthalate-type unsaturated resin), 1g of titanium dioxide slurry (a mixture of 50%wt Lomon Billion R996 titanium dioxide and 50%wt Xinshuangli 5288 unsaturated resin), 1g of defoaming agent (Dongguan Yilian Chemical EL-3555), and 1.6g of the above-mentioned accelerator 1A.

[0036] Step 1: Put the above ingredients into a 1L container and stir at 1000r / min for 5 minutes, then add 650g of aluminum hydroxide powder (Zhongzhou Chalco New Materials H-WF-25B-SP);

[0037] Step 2: Then stir at a speed of 2000-2500 r / min, and heat the resin mixture to 40-45°C through the heat generated by high-speed dispersion;

[0038] Step 3: Then add 3.5g of methyl ethyl ketone peroxide (Nouryon HBO-50), stir at a speed of 1000r / min for 1min, and then transfer to a vacuum device to be stirred. Then, vacuumize and degas for 2min at a low speed of 50-100r / min, release the vacuum and pour the mixture into a casting mold cavity with a PE soft film lining (mold size: 130mm×280mm×15mm), the casting mold cavity is pre-heated to 45°C, and then cover the cast mixture with a PET film to isolate it from the air, and solidify the mixture within 15min;

[0039] Step 4: After the obtained solidified sample block is cooled to room temperature, it is placed in a rotary sander for rough processing, then polished with sandpaper of gradually finer grits, and finally polished with 600# grit to form a test block 1A.

[0040] The accelerator composition of the present invention can form a redox system with peroxide, generate active free radicals at room temperature, thereby initiating the curing and molding of the unsaturated resin-based composite material, and is suitable for continuous casting and intermittent casting processes.

[0041] Example 2

[0042] A UPR artificial stone accelerator composition (accelerator 2A) for resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0043] Table 2 Formula of accelerator 2A in Example 2 of the present invention

[0044] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt naphthenate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 15%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 1.0%wt Anti-yellowing inhibitor Potassium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 80%wt Thickener Cellulose Acetate Butyrate CAB 1.0%wt Thinner Ethylene glycol monobutyl ether margin

[0045] A UPR artificial stone accelerator composition (accelerator 2A) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0046] Preparation: Prepare the raw materials according to the formula ratio;

[0047] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0048] Filtration: Filter through a 100-300 mesh filter to produce accelerator 2A.

[0049] The accelerator 2A sample was used to prepare an experimental test block (test block 2A) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 2A.

[0050] Example 3

[0051] A UPR artificial stone accelerator composition (accelerator 3A) for resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0052] Table 3 Formula of accelerator 3A in Example 3 of the present invention

[0053] raw material specific ingredients Weight Percent Primary Catalyst Promoter Organic phase dispersion or organic phase solution of manganese neodecanoate with a solid content of 5.0%wt 20%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 30%wt Anti-yellowing inhibitor Calcium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 40%wt Thickener Ethyl Cellulose CE 1.0%wt Dispersants BYK-907 1.0%wt Thinner Ethylene glycol methyl ether margin

[0054] A UPR artificial stone accelerator composition (accelerator 3A) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0055] Preparation: Prepare the raw materials according to the formula ratio;

[0056] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the dispersant and the remaining diluent and disperse for 15 minutes;

[0057] Filtration: Filter through a 100-300 mesh filter to produce accelerator 3A.

[0058] The accelerator 3A sample was used to prepare an experimental test block (test block 3A) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 3A.

[0059] Example 4

[0060] A UPR artificial stone accelerator composition (accelerator 4A) for resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0061] Table 4 Formula of accelerator 4A in Example 4 of the present invention

[0062] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt naphthenate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 18% wt Synergist Copper acetate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 1.5%wt Anti-yellowing inhibitor Sodium isooctanoate organic phase dispersion or organic phase solution with a solid content of 10.0%wt 55%wt Thickener Fumed Silica 2.0%wt water Deionized water 3.0%wt Odor masking agent 2-Hexanol 1.0%wt Thinner Ethanol margin

[0063] A UPR artificial stone accelerator composition (accelerator 4A) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0064] Preparation: Prepare the raw materials according to the formula ratio;

[0065] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add water, odor masking agent and the remaining diluent and disperse for 15 minutes;

[0066] Filtration: Filter through a 100-300 mesh filter to produce accelerator 4A.

[0067] The accelerator 4A sample was used to prepare an experimental test block (test block 4A) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 4A.

[0068] Example 5

[0069] A UPR artificial stone accelerator composition (accelerator 5A) for resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0070] Table 5 Formula of accelerator 5A in Example 5 of the present invention

[0071]

[0072] A UPR artificial stone accelerator composition (accelerator 5A) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0073] Preparation of materials: Prepare the raw materials according to the formula ratio;

[0074] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add water, odor masking agent and the remaining diluent and disperse for 15 minutes;

[0075] Filtration: Filter through a 100-300 mesh filter to produce accelerator 4A.

[0076] The accelerator 5A sample was used to prepare an experimental test block (test block 5A) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 5A.

[0077] Example 6

[0078] The accelerator composition of this embodiment is the same as that of embodiment 1.

[0079] The method for making the UPR artificial stone experimental test block (test block 6A) is as follows:

[0080] In the formulation of test block 6A, M18 isophthalic unsaturated resin (Xinshuangli Huizhou Resin Co., Ltd.) was used instead of 5288 orthophthalic unsaturated resin, and the same casting procedure and test block processing procedure as those of test block 1A in Example 1 were used.

[0081] Comparative Example 1

[0082] A UPR artificial stone accelerator composition (accelerator 1B) having excellent resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0083] Table 6 Formula of accelerator 1B in comparative example 1 of the present invention

[0084] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt isooctanoate organic phase dispersion or organic phase solution with a solid content of 12.0%wt 10%wt Anti-yellowing inhibitor Sodium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 85%wt Thickener Fumed Silica 1.0%wt Thinner Isopropyl alcohol margin

[0085] A UPR artificial stone accelerator composition (accelerator 1B) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0086] Preparation of materials: Prepare the raw materials according to the formula ratio;

[0087] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0088] Filtration: Filter through a 100-300 mesh filter to produce Accelerator 1B.

[0089] The accelerator 1B sample was used to prepare an experimental test block (test block 1B) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 1B.

[0090] Comparative Example 2

[0091] A UPR artificial stone accelerator composition (accelerator 2B) having excellent resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0092] Table 7 Formula of accelerator 2B in comparative example 2 of the present invention

[0093] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt isooctanoate organic phase dispersion or organic phase solution with a solid content of 12.0%wt 15%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 0.1%wt Anti-yellowing inhibitor Sodium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 30%wt Thickener Fumed Silica 1.0%wt Thinner Isopropyl alcohol margin

[0094] A UPR artificial stone accelerator composition (accelerator 2B) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0095] Preparation of materials: Prepare the raw materials according to the formula ratio;

[0096] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0097] Filtration: Filter through a 100-300 mesh filter to produce accelerator 2B.

[0098] The accelerator 2B sample was used to prepare an experimental test block (test block 2B) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 2B.

[0099] Comparative Example 3

[0100] A UPR artificial stone accelerator composition (accelerator 3B) having excellent resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0101] Table 8 Formula of accelerator 3B in comparative example 3 of the present invention

[0102] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt isooctanoate organic phase dispersion or organic phase solution with a solid content of 12.0%wt 1.0%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 0.1%wt Anti-yellowing inhibitor Sodium isooctanoate organic phase dispersion or organic phase solution with a solid content of 8.0%wt 98%wt Thickener Fumed Silica 0.5%wt Thinner Isopropyl alcohol margin

[0103] A UPR artificial stone accelerator composition (accelerator 3B) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0104] Preparation: Prepare the raw materials according to the formula ratio;

[0105] Dispersion: At 15-35°C, first add the main catalyst promoter, synergist and anti-yellowing inhibitor to a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0106] Filtration: Filter through a 100-300 mesh filter to produce accelerator 3B.

[0107] The accelerator 3B sample was used to prepare an experimental test block (test block 3B) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 3B.

[0108] Comparative Example 4

[0109] A UPR artificial stone accelerator composition (accelerator 4B) having excellent resistance to yellowing under humidity and heat, comprising the following raw materials by weight percentage:

[0110] Table 9 Formula of accelerator 4B in comparative example 4 of the present invention

[0111] raw material specific ingredients Weight Percent Primary Catalyst Promoter Cobalt isooctanoate organic phase dispersion or organic phase solution with a solid content of 12.0%wt 15%wt Synergist Copper isooctanoate organic phase dispersion or organic phase solution with a solid content of 6.0%wt 0.1%wt Thickener Fumed Silica 0.5%wt Thinner Isopropyl alcohol margin

[0112] A UPR artificial stone accelerator composition (accelerator 4B) with excellent resistance to yellowing under humidity and heat is prepared according to the following method:

[0113] Preparation: Prepare the raw materials according to the formula ratio;

[0114] Dispersion: At 15-35°C, first add the main catalyst promoter and synergist into a suitable dispersion container in sequence under stirring at 200-1000r / min, and disperse for 10 minutes; then add the thickener and disperse for 30 minutes; then add the remaining diluent and disperse for 15 minutes;

[0115] Filtration: Filter through a 100-300 mesh filter to produce accelerator 4B.

[0116] The accelerator 4B sample was used to prepare an experimental test block (test block 4B) using the same formulation, casting procedure, and test block processing procedure as described for preparing test block 1A in Example 1, except that the accelerator in the formulation was replaced with accelerator 4B.

[0117] Reference Example 1

[0118] The accelerator used was cobalt octanoate accelerator LCCA (Shanghai Changfeng Chemical) sold on the market.

[0119] The accelerator LCCA sample was used to prepare an experimental test block (test block 1C) using the same formulation, casting procedure, and test block processing procedure as described for test block 1A, except that the accelerator in the formulation was replaced with a commercially available accelerator LCCA.

[0120] Performance Testing

[0121] For the test blocks 1A, 2A, 3A, 4A, 5A, 6A, 1B, 2B, 3B, 4B and 5C prepared in Examples 1 to 6, Comparative Examples 1 to 4 and Reference Example 1, a high temperature and high humidity test chamber was used to conduct a test of resistance to heat and humidity yellowing (test conditions: parameter setting temperature is 85°C, humidity is 85%RH, and operation is 24h), and the results are shown in Table 10. In addition, a xenon lamp aging tester was used to evaluate the weather resistance according to the standard test of JC / T908-2013, and the results are shown in Table 11.

[0122] Table 10: Test results of heat and humidity aging resistance

[0123]

[0124] Table 11 Xenon lamp aging (JC / T908-2013) test results

[0125]

[0126] In Tables 10 and 11, ΔL is the change in brightness, which is used to reflect the degree of change in brightness of the sample before and after aging;

[0127] △a is the amount of color change on the red-green axis (a-axis). A positive △a indicates that the sample has become redder, and a negative △a indicates that the sample has become greener.

[0128] △b is the amount of color change on the yellow-blue axis (b axis). A positive △b may indicate that the sample has become more yellow, while a negative △b may indicate that the sample has become more blue.

[0129] △E is the degree of color difference before and after the test. The smaller the value, the closer the color is and the smaller the visual difference is. The larger the value, the more obvious the color change is and the greater the visual difference is. Its value is obtained by adding the squares of △L, △a, and △b and then taking the square root, that is:

[0130]

[0131] According to the results of the moisture and heat aging resistance of Examples 1 to 6, Comparative Examples 1 to 4 and Reference Example 1 (Table 10), the accelerator composition provided by the present invention has a significantly improved moisture and heat yellowing resistance effect compared with similar accelerators on the market. At the same time, the xenon lamp aging test results (Table 11) are also significantly better than similar accelerators on the market.

[0132] The accelerator composition of the present invention can be widely used in the production of artificial stone products of UPR unsaturated resin system, including UPR artificial stone solid surface materials, UPR artificial stone sanitary casting products, etc. The unsaturated resin (UPR)-based composite material products (artificial stones) prepared or produced by using the accelerator composition of the present invention are not easy to yellow in color appearance and decorative effect, are resistant to climate aging such as humidity and heat, and have excellent external light color long-term retention, showing excellent competitiveness in the application of unsaturated resin (UPR)-based artificial stones in the market.

[0133] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A UPR artificial stone accelerator composition for resistance to yellowing due to humidity and heat, characterized in that: According to weight percentage, the promoter composition comprises: 3.0-35.0%wt of a primary catalytic promoter, 0.0-30.0%wt of a synergist, 55.0-97.0%wt of a yellowing inhibitor, 0.0-2.0%wt of a thickener, 0.0-3.0%wt of water and 0.0-1.0%wt of a functional additive, and the balance is a diluent; The anti-yellowing inhibitor comprises component A, and component A is one or more of organic carboxylic acid sodium salt, organic carboxylic acid potassium salt, and organic carboxylic acid calcium salt.

2. The UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to claim 1, characterized in that: The component A is one or more of potassium isooctanoate, sodium isooctanoate and calcium isooctanoate.

3. The UPR artificial stone accelerator composition for resistance to yellowing due to humidity and heat according to claim 1 or 2, characterized in that: The anti-yellowing inhibitor is an organic phase dispersion or organic phase solution formed by mixing the component A with an organic solvent B, the solid content of the component A is 3.0-15.0%wt, and the organic solvent B is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid.

4. The UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to claim 1, characterized in that: The main catalyst promoter is an organic phase dispersion or organic phase solution formed by mixing a metal carboxylate and an organic solvent C, the solid content of the metal carboxylate is 3.0-15.0%wt, and the organic solvent C is at least one of a benzene organic solvent, a ketone organic solvent, an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and an organic carboxylic acid.

5. The UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to claim 4, characterized in that: The metal carboxylate is one or more of iron naphthenate, cobalt naphthenate, manganese naphthenate, cobalt isooctanoate, zinc isooctanoate, zinc neodecanoate, and manganese neodecanoate.

6. The UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to claim 1, characterized in that: The synergist is an organic phase dispersion or an organic phase solution formed by mixing an organic carboxylic acid copper salt and an organic solvent D, wherein the organic carboxylic acid copper salt is one or more of copper acetate and copper isooctanoate, the solid content of the organic carboxylic acid copper salt is 3.0 to 12.0%wt, and the organic solvent D is at least one of an alcohol organic solvent, an ester organic solvent, an ether organic solvent, and isooctanoic acid.

7. The UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to claim 1, characterized in that: The thickener is one or more of ethyl cellulose, cellulose acetate butyrate, and fumed silica.

8. The UPR artificial stone accelerator composition for resistance to yellowing due to humidity and heat according to claim 1, characterized in that: The functional additive is one or more of a dispersant, a leveling agent, and an odor masking agent.

9. The method for preparing the UPR artificial stone accelerator composition for resistance to wet-heat yellowing according to any one of claims 1 to 8, characterized in that: Firstly, a main catalytic promoter, a synergist and a yellowing resistance inhibitor are measured and added into a dispersion container in sequence according to a formula ratio, and dispersed for 10 to 30 minutes under a stirring state at a speed of 200 to 1000 r / min in an environment of 15 to 35 DEG C; then a thickener is added and dispersed for 30 to 60 minutes; then water, a functional additive and a remaining amount of a diluent are added in sequence and dispersed for 10 to 30 minutes; finally, a 100 to 300 mesh filter is used to filter to obtain a promoter composition.

10. Use of the accelerator composition for resistance to yellowing of UPR artificial stone under humidity and heat according to any one of claims 1 to 8 or the accelerator composition prepared by the preparation method according to claim 9 in the preparation of UPR artificial stone.